2007
DOI: 10.1080/10910340701696864
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Mechanics Approach to Machining at High Speeds: Part I: Justification of Potential Flow Models

Abstract: & The need throughout the machining industry for cost reduction and increases in productivity has contributed to new interest in high-speed machining. Even though many models for machining exist, most of them are for low-speed machining, where momentum is negligible and material behavior is well approximated by quasi-static constitutive laws. In machining at high speeds, momentum can be important, and the strain rate can be exceedingly high. For these reasons, a fluid mechanics approach to understanding high-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Through a perturbation series approach to the Navier-Stokes equations, it is possible to show that potential flow can be used as a first approximation to model high-speed, very high-speed, or ultra-high-speed machining events, as the authors have shown in the first part of this study (Kazban and Mason, 2007). This surprising, new conclusion is dependent upon several assumptions, including…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Through a perturbation series approach to the Navier-Stokes equations, it is possible to show that potential flow can be used as a first approximation to model high-speed, very high-speed, or ultra-high-speed machining events, as the authors have shown in the first part of this study (Kazban and Mason, 2007). This surprising, new conclusion is dependent upon several assumptions, including…”
Section: Introductionmentioning
confidence: 78%
“…0). Additional terms in the perturbation series add additional complexity and make this solution more accurate for larger Re (for details, see Kazban and Mason, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of OHP, the reverse polarized could travel to the bulk liquid. For instance, the flowing liquid was viscid, and incompressible by the Newtonian liquid, then peristaltic flow at the PF-TENG cell-liquid interface, the continuity and Navier Stokes equations clench worthy and can be modified for the ion's drive in the IHP 51 , 52 . where ρ and υ fluid remain the density, and velocity of the working fluid, correspondingly.…”
Section: Resultsmentioning
confidence: 99%
“…Kazban [23] studied the change in the flow stress of duplex stainless steel with the strain rate and found that the change in flow stress is similar to that of a Newtonian fluid after a certain strain rate value. The comparison of stress-strain rate relationship between duplex stainless steel and a Newtonian fluid is shown in Figure 2.…”
Section: Shear Zone Analysismentioning
confidence: 99%